2019
DOI: 10.1029/2019gc008181
|View full text |Cite
|
Sign up to set email alerts
|

Crustal Azimuthal Anisotropy Beneath the Central North China Craton Revealed by Receiver Functions

Abstract: To characterize crustal anisotropy beneath the central North China Craton (CNCC), we apply a recently developed deconvolution approach to effectively remove near‐surface reverberations in the receiver functions recorded at 200 broadband seismic stations and subsequently determine the fast orientation and the magnitude of crustal azimuthal anisotropy by fitting the sinusoidal moveout of the P to S converted phases from the Moho and intracrustal discontinuities. The magnitude of crustal anisotropy is found to ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 80 publications
2
23
0
Order By: Relevance
“…Therefore, from splitting measurements alone, we are not able to quantitatively analyze the splitting pattern with respect to back azimuth and rule out the possibility of a multilayered anisotropy structure in the lithosphere and asthenosphere. Although the crustal contribution to the observed splitting delay time could be significant in some areas (e.g., Reiss et al, 2016), receiver function analyses imply that accumulated delay time due to crustal anisotropy is ~0.20 s beneath the WNCC and TNCO (Xu et al, 2018; Yang et al, 2018; Zheng et al, 2019). This is significantly smaller than the regional average, suggesting that the upper mantle is the primary source of the observed anisotropy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, from splitting measurements alone, we are not able to quantitatively analyze the splitting pattern with respect to back azimuth and rule out the possibility of a multilayered anisotropy structure in the lithosphere and asthenosphere. Although the crustal contribution to the observed splitting delay time could be significant in some areas (e.g., Reiss et al, 2016), receiver function analyses imply that accumulated delay time due to crustal anisotropy is ~0.20 s beneath the WNCC and TNCO (Xu et al, 2018; Yang et al, 2018; Zheng et al, 2019). This is significantly smaller than the regional average, suggesting that the upper mantle is the primary source of the observed anisotropy.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of crustal deformation is important in understanding the tectonic evolution and seismic hazards in this study area. However, the details on crustal deformation beneath the TNCO and its adjacent areas are still being discussed and debated recently (Tian and Zhao, 2013;Zhang et al, 2016;Yang et al, 2018;Schellart et al, 2019;Zheng et al, 2019;Cai et al, 2021;Chang et al, 2021). Further studies on crustal structure and anisotropy are essential for constraining the crustal deformation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these methods, crustal anisotropy beneath the southeastern and northeastern Tibetan plateau was calculated to investigate the mechanism of the crustal deformation and thickening (Sun et al, 2012;Wang et al, 2016;Xu et al, 2018). Yang et al (2018) and Zheng et al (2019) also measured the splitting of the Moho Ps phases from receiver functions and observed the spatial distribution of crustal anisotropy beneath the northeastern TNCO, respectively. Results mentioned above confirmed that crustal anisotropy has been successfully estimated from the splitting of the Moho Ps phases and performed to study the crustal deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies revealed the velocity structure and seismic anisotropy beneath the crust and upper mantle of the NCC [23,[25][26][27]. However, these results on understanding the lithospheric thinning and deformation of the NCC are still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Seismic anisotropy is often used to investigate the deformation of the crust and upper mantle. The S-wave splitting studies provide useful information about anisotropy in the crust and upper mantle [24,26]. However, the depth of the anisotropic structure is usually difficult to obtain by S-wave splitting.…”
Section: Introductionmentioning
confidence: 99%